The Implications of the Activating Defense Law No.13 of 1992 on Human Rights in Jordanian Society - The Corona pandemic as a model - Alodainat, Dalal Shawkat; Alquisi, Salim Ahmad (Journal of Humanities & Social Sciences, 2023)
The study aimed to identify the implications of the application of orders to defend human rights in Jordanian society, The research used the descriptive survey approach, and qualitative approach, and relied on the questionnaire and interview tools to find out those objectives. A quantitative and qualitative data have been collected through in-depth interviews with a number of specialists and experts. other special information has been collected from the study sample consisting of (400) citizens and residents of Jordanian society institutions in Karak governorate and specifically individuals affected by the Corona pandemic, and 4 individuals of specialists and experts in human rights and decision-making were interviewed, The results showed a relationship between the overall degree of the dimension of of positive effects as one of the mitral effects on the application of defense orders,The results also showed that the general level of responses of the study sample of individuals affected by the Corona pandemic in the institutions of Jordanian society (Karak Governorate) towards the level of human rights in Jordanian society has come at a high level. The study recommended through its field results a number of recommendations.